Kegiatan Penyuluhan Dan Penapisan Komposisi Tubuh Pada Kelompok Lanjut Usia Di Gereja St. Fransiskus Asisi - Limas, Peter Ian; Kasvana Kasvana; Saerang, Stefanus Hnady; Satyanegara, William Gilbert; Wijaya, Dean Ascha; Santoso, Alexander Halim (STIKes Ibnu Sina Ajibarang, 2024)
Aging is associated with significant changes in body composition, specifically a decrease in lean body mass and an increase in fat mass. These changes contribute to the prevalence of obesity and sarcopenia in the elderly population, impacting quality of life, morbidity and mortality. A complex interaction between hormonal decline, chronic inflammation, nutritional deficiencies, and reduced physical activity underlies these changes. This activity uses the PDCA (Plan-Do-Check-Act) methodology to screen for obesity and sarcopenia in the elderly at St. Mary's Church, Francis of Assisi. We use Bioelectrical Impedance Analysis (BIA) to measure body composition, which includes total body fat, visceral fat, subcutaneous fat, and muscle mass. Among 32 participants, the average total body fat, visceral fat, subcutaneous fat, and muscle mass were 36.5% each; 9.6%; 9.68%; and 21.5%. Body composition assessment using BIA is very important in managing the elderly's health. Preventive strategies, including tailored exercise programmes, nutritional counselling, and lifestyle modifications, are essential to maintain muscle mass and prevent excessive fat deposition, thereby improving quality of life and reducing morbidity and mortality. Keywords: Body Composition, Obesity, Sarcopenia, Elderly, Bioelectrical Impedance Analysis